Hubungan Antara Gangguan Pendengaran dengan Prestasi Akademik Siswa Kelas VI di Sekolah Dasar Muhammadiyah 8 Medan - Tekto Yudo Frassetyo Darmito; Muhammad Edy Syahputra Nasution; Siti Masliana Siregar; Desi Isnayanti (Buletin Farmatera, 2018)
Abstract : There are 278 million people affected by hearing loss in the world. The absorption of information by listening is greater than reading. Primary school students with hearing loss have difficulty in learning various aspects of verbal communication compared to normal children. The purpose of this study is to determine the relationship between the hearing loss with the achievement of grade 6 students of a primary school. This is an analytical study with a cross-sectional approach to 52 students. The data obtained from physical examination of the ear, tuning fork examination, pure tone audiometry examination, and student’s academic achievement report cards. Hearing function, degree of hearing loss, and academic achievement in each subject are described in descriptive statistics. Fisher exact test is used to find the relationship between hearing loss and academic achievement in every subject at school. There was a significant relationship between hearing loss and academic achievement based on Indonesian subjects (p = 0,013), English (p = 0,026), and mathematics (p = 0,007). There is a significant relationship between the hearing loss and the achievement of grade 6 students of the primary school.Keywords: academic achievement, hearing disorder, primary school